Hepatitis A Virus in Food Detection and Inactivation Methods - Sánchez, Glòria. (SpringerBriefs in Food, Health, and Nutrition,, 2013)
Hepatitis A virus (HAV) is responsible for around half of the total number of hepatitis infections diagnosed worldwide. HAV infection is mainly propagated via the fecal-oral route, and as a consequence of globalization, transnational outbreaks of foodborne infections are reported with increasing frequency. Therefore, in this review, state-of-the-art information on the molecular procedures for HAV detection in food, and the efficacy of common food manufacturing processes are compiled. The purpose of this Brief is to consolidate basic information on various aspects of HAV and to provide a guideline for its prevention and control across the food supply chain from pre-harvest to manufacturing.